2005
DOI: 10.1007/s00109-005-0015-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel sequence variants in the TMIE gene in families with autosomal recessive nonsyndromic hearing impairment

Abstract: To date, 37 genes have been identified for nonsyndromic hearing impairment (NSHI). Identifying the functional sequence variants within these genes and knowing their population-specific frequencies is of public health value, in particular for genetic screening for NSHI. To determine putatively functional sequence variants in the transmembrane inner ear (TMIE) gene in Pakistani and Jordanian families with autosomal recessive (AR) NSHI, four Jordanian and 168 Pakistani families with ARNSHI that is not due to GJB2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…It is likely that the putatively cytoplasmic region of Tmie is essential to its function. Human mutations that disrupt arginine residues there lead to profound hearing loss (23,24). This highly charged E region could serve, for example, as a site of interaction with other proteins that have a direct role in mechanotransduction.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the putatively cytoplasmic region of Tmie is essential to its function. Human mutations that disrupt arginine residues there lead to profound hearing loss (23,24). This highly charged E region could serve, for example, as a site of interaction with other proteins that have a direct role in mechanotransduction.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the TMIE gene have been shown to cause nonsyndromic, recessively inherited hearing loss [5,9]. In the present study, we found that two novel variants (g.1-219A > T and c.257G > A) of TMIE gene in the patients are heterozygous, with one variant and one normal allele.…”
Section: Discussionmentioning
confidence: 66%
“…As a result, an altered TMIE protein leads to its loss of function. In addition, it has also been shown that variants in TMIE residues R81, R84 and R92 are associated with nonsyndromic hearing loss [5,9]. Protein phosphorylation plays a central role in many biological phenomena [24].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations